2010
DOI: 10.1016/j.ijgo.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous nitroglycerin for controlled cord traction in the management of retained placenta

Abstract: Intravenously administered nitroglycerin did not facilitate the release of retained placenta by umbilical cord traction. However, cord traction may be performed longer than 30 minutes to attempt releasing the placenta before operative manual removal is initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Much effort has been gone into finding alternative measures for management of retained placenta and associated PPH (Table ) but there are few randomized trials, with a small number of participants. Nitroglycerine orally, intravenously or intra‐umbilically, has been reported as either highly successful or ineffective . Intravenous sulprostone, described by Van Beekhuizen, reduced the number of manually removed placentas by 49% .…”
Section: Discussionmentioning
confidence: 99%
“…Much effort has been gone into finding alternative measures for management of retained placenta and associated PPH (Table ) but there are few randomized trials, with a small number of participants. Nitroglycerine orally, intravenously or intra‐umbilically, has been reported as either highly successful or ineffective . Intravenous sulprostone, described by Van Beekhuizen, reduced the number of manually removed placentas by 49% .…”
Section: Discussionmentioning
confidence: 99%
“…However, this trial involved only 24 women and a subsequent larger study by the same team showed no significant benefit . Another small trial of intravenous nitroglycerin also demonstrated no benefit . We await with interest the outcome of the UK‐wide randomized controlled trial on the use of glycerin trinitrate for RP (GOT‐IT Trial).…”
Section: Conflicting Guidancementioning
confidence: 97%
“…Literature Findings: Randomized controlled trials comparing IV or sublingual nitroglycerin with placebo for the purpose of uterine relaxation report inconsistent findings for the successful removal of retained placenta (Category A2-E evidence). [123][124][125] Observational studies and case reports indicate successful uterine relaxation and successful placental removal after IV or sublingual nitroglycerin administration (Category B3/B4 evidence). [126][127][128][129][130] Survey Findings: The ASA members agree and the consultants strongly agree that nitroglycerin may be used as an alternative to terbutaline sulfate or general endotracheal anesthesia with halogenated agents for uterine relaxation during removal of retained placental tissue.…”
Section: Nitroglycerin For Uterine Relaxationmentioning
confidence: 99%